2021
DOI: 10.3390/en14165162
|View full text |Cite
|
Sign up to set email alerts
|

The Methodology for Designing Residential Buildings with a Positive Energy Balance—Case Study

Abstract: The article presents the results of the application of an original methodology for designing residential buildings with a positive energy balance in accordance with the principles of sustainable development. The methodology was verified using a computational example involving the selection of a compromise solution for a single-family residential building with a positive energy balance located in Warsaw, Poland. Three different models of decision-makers’ preferences were created, taking into account selected de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The introduction to the work presents information on the energy transformation of buildings towards low-energy buildings. In the future, it will lead to the construction of nearly zero energy buildings (nZEB) or even plus energy buildings-as indicated by the case study showing the methodology of designing such facilities [63]. The results of this analysis showed that with the reduction of the thermal power for heating and ventilation purposes, the proportions between the peak power for these purposes and the power necessary for the preparation of domestic hot water changed significantly, as shown in Figure 6.…”
Section: Discussionmentioning
confidence: 95%
“…The introduction to the work presents information on the energy transformation of buildings towards low-energy buildings. In the future, it will lead to the construction of nearly zero energy buildings (nZEB) or even plus energy buildings-as indicated by the case study showing the methodology of designing such facilities [63]. The results of this analysis showed that with the reduction of the thermal power for heating and ventilation purposes, the proportions between the peak power for these purposes and the power necessary for the preparation of domestic hot water changed significantly, as shown in Figure 6.…”
Section: Discussionmentioning
confidence: 95%
“…Three principles were followed in the process of indicator selection. First, the evaluation indexes should reasonably reflect the current stage of development of prefabricated buildings and meet the development requirements of prefabricated buildings [28]. Second, the selection of evaluation indicators for prefabricated buildings should be done from a holistic perspective.…”
Section: Construction Of Evaluation Index System Based On Dpsir Modelmentioning
confidence: 99%
“…Passive buildings are the latest generation of energy-efficient buildings [7][8][9]. They offer the highest thermal comfort and satisfy extremely low demand for thermal energy, maximum 15 kWh/m 2 /year (less than 1.5 litres of heating oil or 1.5 m 3 of natural gas per m 2 /year), or 5 kWh of electricity generated with a heat pump [10].…”
Section: Introductionmentioning
confidence: 99%